(untitled) (Marketing Journal, 2025)
The article analyzes theoretical approaches to assessing the economic efficiency of digital transformation in the regional construction system. The impact of digital technologies on efficiency, cost -optimization factors, and the conceptual theoretical mode l for evaluation are substantiated.